Inverse Scattering Construction of Dipole Black Rings - Rocha, J.; Rodriguez, M.J.; Varela, O.; Virmani, A. (Springer Proceedings in Mathematics and Statistics, 2014)
We describe an approach Lo systematically generate regular and asymptotically flat dipole black rings in a 5D Einstein Maxwell-dilaton theory obtained from 6D vacuum gravity by Kaluza-Klein reduction. Our construction employs the inverse scattering method in six dimensions. We illustrate the scheme with the explicit construction of the singly-spinning dipole ring. These techniques can also be used to generate more general five-dimensional black ring solutions, displaying rotation along the two orthogonal planes, electric charge and magnetic dipole charge.